2015
DOI: 10.1088/1367-2630/17/6/065008
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic cost of creating correlations

Abstract: We investigate the fundamental limitations imposed by thermodynamics for creating correlations. Considering a collection of initially uncorrelated thermal quantum systems, we ask how much classical and quantum correlations can be obtained via a cyclic Hamiltonian process. We derive bounds on both the mutual information and entanglement of formation, as a function of the temperature of the systems and the available energy. While for a finite number of systems there is a maximal temperature allowing for the crea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 64 publications
2
121
0
Order By: Relevance
“…[52][53][54][55][56][57][58][59], for a variety of settings, including unitary and non-unitary processes. For example, the thermodynamic efficiency of an engine operating on pairs of correlated atoms can be quantified in terms of quantum discord and it was shown to exceed the classical efficiency value [54].…”
Section: Work From Correlationsmentioning
confidence: 99%
See 3 more Smart Citations
“…[52][53][54][55][56][57][58][59], for a variety of settings, including unitary and non-unitary processes. For example, the thermodynamic efficiency of an engine operating on pairs of correlated atoms can be quantified in terms of quantum discord and it was shown to exceed the classical efficiency value [54].…”
Section: Work From Correlationsmentioning
confidence: 99%
“…In [60] the minimal heat dissipation for coupling a harmonic oscillator that starts initially in local thermal equilibrium, and ends up correlated with a bath of harmonic oscillators in a global thermal equilibrium state, is determined and it was shown that this heat contribution resolves a previously reported second law violation. Thermodynamic aspects of creating correlations are also studied in [59] where the minimum work cost is established for unitarily evolving an initial, locally thermal, state of N systems to a global correlated state. A maximum temperature is derived at which entanglement can still be created, along with the minimal associated energy cost.…”
Section: Work From Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as recently shown by Huber et al [41], N-qubit thermal states of arbitrarily high temperatures and N sufficiently large (represented, in the computational basis, by diagonal density matrices arbitrarily close to the identity, hence fulfilling (28)) can acquire GM-entanglement by means of rotations to Dicke-like (non-X) states, thus providing a counter-example to the original conjecture.…”
Section: X-mems With Respect To Spectrummentioning
confidence: 90%